2023
DOI: 10.1038/s41467-023-39028-w
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage targeting microbiota alleviates non-alcoholic fatty liver disease induced by high alcohol-producing Klebsiella pneumoniae

Abstract: Our previous studies have shown that high alcohol-producing Klebsiella pneumoniae (HiAlc Kpn) in the intestinal microbiome could be one of the causes of non-alcoholic fatty liver disease (NAFLD). Considering antimicrobial resistance of K. pneumoniae and dysbacteriosis caused by antibiotics, phage therapy might have potential in treatment of HiAlc Kpn-induced NAFLD, because of the specificity targeting the bacteria. Here, we clarified the effectiveness of phage therapy in male mice with HiAlc Kpn-induced steato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Our results suggest the potential association of endogenous EtOH production by digestive microorganisms and NASH, and the use of new therapeutic avenues such as antibiotics ( E. bolteae is expected to be sensitive to rifaximin which is effective in NASH in some studies ( Abdel-Razik et al., 2018 2018 ; Boehme et al., 2023 2023 ), fecal transplantation or the use of phage therapy targeting E. bolteae as described by Yuan et al. with Klebsiella pneumoniae ( Gan et al., 2023 ). Future studies will determine ethanol production by the 12 species (81 strains) enriched in NASH patients.…”
Section: Discussionmentioning
confidence: 57%
“…Our results suggest the potential association of endogenous EtOH production by digestive microorganisms and NASH, and the use of new therapeutic avenues such as antibiotics ( E. bolteae is expected to be sensitive to rifaximin which is effective in NASH in some studies ( Abdel-Razik et al., 2018 2018 ; Boehme et al., 2023 2023 ), fecal transplantation or the use of phage therapy targeting E. bolteae as described by Yuan et al. with Klebsiella pneumoniae ( Gan et al., 2023 ). Future studies will determine ethanol production by the 12 species (81 strains) enriched in NASH patients.…”
Section: Discussionmentioning
confidence: 57%
“… 85 Moreover, oral treatment with a single phage led to the alleviation of HiAlc Kpn-induced steatohepatitis in mice. 106 In a similar preclinical study targeting K. pneumoniae , Ichikawa et al. found that Th17 cell responses were induced by PSC-derived K. pneumoniae , which accelerated liver injury in hepatobiliary injury-prone mice.…”
Section: Precise Editing Of the Intestinal Bacterial Microbiota By Ph...mentioning
confidence: 99%
“…Finally, selective elimination of the HiAlc Kpn strain before focal microbiome transplantation prevents NAFLD in recipient mice [ 123 ]. Other data suggest that phage therapy targeting the gut microbiota is an alternative to antibiotics, with potential efficacy and safety, at least in HiAlc Kpn -induced NAFLD [ 124 ]. In NASH patients, an increased abundance of alcohol-producing bacteria corresponds to an elevated blood ethanol concentration, suggesting a role for alcohol-producing microbiota in the pathogenesis of NASH [ 125 ].…”
Section: The Gut Microbiome: a Key Regulator Of Host Physiologymentioning
confidence: 99%